The Role of Educators in Character Education for Students with Learning Disabilities Who Are in Conflict with the Law at the Yogyakarta Class II LPKA (Jurnal Orthopaedagogia, 2025)
Character education for emotionally disturbed students (peserta didik tunalaras) in conflict with the law at the Special Child Development Institution (LPKA) Class II Yogyakarta is an essential part of the social rehabilitation process. This study aims to analyze the role of educators in supporting character education for these students, the strategies applied in managing learning, and the challenges faced. This research employs a qualitative phenomenological approach with data collection techniques including interviews, observations, and document studies. The results show that educators at LPKA play roles as academic learning facilitators, character mentors, and psychosocial motivators. The strategies implemented include contextual learning, integration of psychosocial approaches, curriculum adaptation, and adjustments based on students' backgrounds. However, the educational process still faces challenges such as limited human resources, low learning motivation among students, background disparities, inadequate learning facilities, and inconsistent collaboration with external parties. These findings indicate the need to strengthen educators' competencies, improve learning facilities, and enhance cross-sector collaboration to support the success of character education at LPKA.